2021
DOI: 10.3389/fcimb.2021.765266
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Substrate-Binding Sites in the Phosphatidylserine Synthase in Candida albicans

Abstract: The fungal phosphatidylserine (PS) synthase, a membrane protein encoded by the CHO1 gene, is a potential drug target for pathogenic fungi, such as Candida albicans. However, both substrate-binding sites of C. albicans Cho1 have not been characterized. Cho1 has two substrates: cytidyldiphosphate-diacylglycerol (CDP-DAG) and serine. Previous studies identified a conserved CDP-alcohol phosphotransferase (CAPT) binding motif, which is present within Cho1. We tested the CAPT motif for its role in PS synthesis by mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(35 citation statements)
references
References 53 publications
1
34
0
Order By: Relevance
“…As an initial step to directly evaluate whether these serine probes interact with PS biosynthetic machinery, we assessed their ability to inhibit the activity of PS synthase (Cho1p) from C. albicans for the conversion of natural serine to PS. These experiments were performed using C. albicans cells because this organism is similar to S. cerevisiae in terms of the PS biosynthetic pathway and its PS synthase enzyme (alignment of Ca Cho1 and Sc Cho1 amino acid sequences in Clustal Omega revealed 60.52% sequence identity), and because we have previously developed a robust assay utilizing cell membrane extracts containing Cho1p to convert tritium-labeled serine ( 3 H-serine) and CDP-DAG into isotopically labeled PS ( 3 H-PS). ,, These experiments showed that 3 H-PS production was diminished by probes N- l -SerN 3 and C- l -SerN 3 in a dose-dependent manner (Figure ). Statistical analysis showed that both N- l -SerN 3 and C- l -SerN 3 displayed significantly decreased enzyme activity for all concentrations tested (1, 5, 10, and 25 mM).…”
Section: Resultsmentioning
confidence: 99%
“…As an initial step to directly evaluate whether these serine probes interact with PS biosynthetic machinery, we assessed their ability to inhibit the activity of PS synthase (Cho1p) from C. albicans for the conversion of natural serine to PS. These experiments were performed using C. albicans cells because this organism is similar to S. cerevisiae in terms of the PS biosynthetic pathway and its PS synthase enzyme (alignment of Ca Cho1 and Sc Cho1 amino acid sequences in Clustal Omega revealed 60.52% sequence identity), and because we have previously developed a robust assay utilizing cell membrane extracts containing Cho1p to convert tritium-labeled serine ( 3 H-serine) and CDP-DAG into isotopically labeled PS ( 3 H-PS). ,, These experiments showed that 3 H-PS production was diminished by probes N- l -SerN 3 and C- l -SerN 3 in a dose-dependent manner (Figure ). Statistical analysis showed that both N- l -SerN 3 and C- l -SerN 3 displayed significantly decreased enzyme activity for all concentrations tested (1, 5, 10, and 25 mM).…”
Section: Resultsmentioning
confidence: 99%
“…To further validate the inhibitory effects of the six molecules on Cho1, a radioactive PS synthase assay was conducted on Cho1 in the presence of these compounds. Unlike the malachite green-based assay, the radioactive PS synthase assay directly measures the incorporation of L-[ 3 H]-serine into PS in the lipid phase (26, 33, 47). The radioactive PS synthase assay was performed on purified Cho1 in the presence of the six compounds at 100 μM, and all six molecules were shown to totally inhibit Cho1 (Figure 3A), consistent with the screening results.…”
Section: Resultsmentioning
confidence: 99%
“…PS is the lipid precursor for making phosphatidylethanolamine (PE), an essential phospholipid, via the de novo pathway. Growth can resume when PS synthesis is inhibited, albeit more slowly, if the organism is able to make PE from ethanolamine acquired from the medium via the salvage (Kennedy) pathway (14, 26). Thus, ethanolamine-dependent growth in minimal media is a characteristic phenotype of PS synthesis loss.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations